2023
DOI: 10.1057/s41599-023-01506-3
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of translating swear words into Arabic: a case study of a parallel corpus of Netflix English-Arabic movie subtitles

Abstract: This study adopts a corpus-assisted approach to explore the translation strategies that Netflix subtitlers opted for in rendering 1564 English swear words into Arabic. It uses a 699,229-word English-Arabic parallel corpus consisting of the English transcriptions of forty English movies, drama, action, science fiction (sci-fi), and biography and their Arabic subtitles. Using the wordlist tool in SketchEngine, the researchers identified some frequent swear words, namely fuck, shit, damn, ass, bitch, bastard, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Roughly, the same results were found by Abu-Rayyash et al (2023), who investigated translation strategies chosen by Netflix subtitlers to render 1564 swearwords from English into Arabic. Noticeably, these studies and other further ones (see Al-Zgoul and Al-Salman, 2022;Debbas and Haider, 2020;Al-Yasin and Rabab'ah, 2019;Al-Jabri, 2021) stress the fact that, in most cases, subtitlers' acts are marked by opting for omission and euphemism strategies.…”
Section: Empirical Studiessupporting
confidence: 69%
See 1 more Smart Citation
“…Roughly, the same results were found by Abu-Rayyash et al (2023), who investigated translation strategies chosen by Netflix subtitlers to render 1564 swearwords from English into Arabic. Noticeably, these studies and other further ones (see Al-Zgoul and Al-Salman, 2022;Debbas and Haider, 2020;Al-Yasin and Rabab'ah, 2019;Al-Jabri, 2021) stress the fact that, in most cases, subtitlers' acts are marked by opting for omission and euphemism strategies.…”
Section: Empirical Studiessupporting
confidence: 69%
“…This load varies significantly due to different linguistic, historical, and cultural contexts. Accordingly, translators are accountable for dealing with the translational burden triggered by such cultural nuances and communicating them thoughtfully, taking into consideration the most appropriate translation norms of the translating language (Abu Rayyash et al, 2023).…”
Section: Empirical Studiesmentioning
confidence: 99%
“…The study concluded that the majority of metaphorical expressions in the subtitles are lexicalized and conventional, aiming to enhance reader accessibility. Additionally, Abu-Rayyash et al . (2023) utilized a corpus-assisted approach to examine the translation strategies employed by Netflix subtitlers when rendering 1,564 English swear words into Arabic.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The presence of taboo words, e.g., expletives, swear words and vulgarisms, can be attested in the majority of languages and cultures worldwide (Abu-Rayyash, Haider, and Al-Adwan 2023). They are to be avoided entirely, especially in mixed or polite company.…”
Section: 1mentioning
confidence: 99%